2022
DOI: 10.1371/journal.pdig.0000014
|View full text |Cite
|
Sign up to set email alerts
|

Transfer learning for non-image data in clinical research: A scoping review

Abstract: Background Transfer learning is a form of machine learning where a pre-trained model trained on a specific task is reused as a starting point and tailored to another task in a different dataset. While transfer learning has garnered considerable attention in medical image analysis, its use for clinical non-image data is not well studied. Therefore, the objective of this scoping review was to explore the use of transfer learning for non-image data in the clinical literature. Methods and findings We systematica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 125 publications
0
21
0
Order By: Relevance
“…To test the resulting CNN, we used the so-called leave-one-out cross-validation. 35,36 This technique is used for small data sets. It is based on the training of the network on n – 1 data sets (n = 14) and using the remaining data points as a test sample.…”
Section: Methodsmentioning
confidence: 99%
“…To test the resulting CNN, we used the so-called leave-one-out cross-validation. 35,36 This technique is used for small data sets. It is based on the training of the network on n – 1 data sets (n = 14) and using the remaining data points as a test sample.…”
Section: Methodsmentioning
confidence: 99%
“…Existing ACC models may potentially become inapplicable as ICD-11 and other updated code sets are implemented. Transitions of code sets could require new methods of data handling and mapping 14 , 15 .…”
Section: Challenges With Accmentioning
confidence: 99%
“…However, transfer learning has yet to be well studied with non-image data in the clinical literature, where a limited number of studies have been published in a recent review (Ebbehoj et al, 2022), where the authors found that studies primarily used time-series data (n = 51, 61%), with ne-tuning being the most common transfer learning strategy (70%), followed by feature representation transfer (22%). Seven studies out of 83 used both approaches.…”
Section: Transfer Learning In MLmentioning
confidence: 99%